PENGARUH INDEKS PEMBANGUNAN MANUSIA (IPM) DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA BARAT - Nadilla; Nindia Gracella; Della Gustina; Frenzi Susilawati; Nindi Dia Sapitri; Ansofino (Smart Education, 2026)
This study aims to examine the influence of the Human Development Index (HDI) and Government Expenditure (PP) on economic growth in West Sumatra Province. The data used is panel data covering 19 districts/cities during the 2020–2024 period, with a total of 95 observations. The research data is sourced from the Central Statistics Agency (BPS) and analyzed using the Fixed Effect Model (FEM) through the Panel Least Squares method. The analysis results show that simultaneously, the HDI and government expenditure have a significant influence on economic growth. Partially, the HDI is proven to have a positive and significant effect on economic growth, indicating that improving the quality of human resources through education, health, and public purchasing power plays an important role in driving regional economic growth. Conversely, government expenditure has a positive but insignificant effect on economic growth. These findings indicate that government expenditure in West Sumatra Province has not been fully optimal in driving economic growth during the study period. Therefore, improving the quality of human development is a key factor in accelerating economic growth, while the effectiveness of management and allocation of government expenditure needs to be continuously improved to provide a more optimal impact on the regional economy.